Neuroblastoma, Body Mass Index, and Survival. Issue 14 (April 2015) - Small, Annabel G.; Thwe, Le M.; Byrne, Jennifer A.; Lau, Loretta; Chan, Albert; Craig, Maria E.; Cowell, Chris T.; Garnett, Sarah P.; Segura., Miguel F
<x xml:space="preserve">Abstract</x> Abstract Extremes of body mass index (BMI) at diagnosis of childhood cancers have been associated with poorer prognosis. The aims of this retrospective review were to examine the growth and BMI status of children diagnosed with neuroblastoma (NB) and determine if BMI status at diagnosis affected survival. Between 1985 and 2005, 154 children were diagnosed with NB at Sydney Children's Hospitals Network (Westmead), Australia, of which 129 had both length/height and weight recorded in the medical records at diagnosis. BMI was calculated and children were classified as underweight (BMI <15th percentile), normal weight, and overweight (BMI >85th percentile). Disease stage was classified according to the International NB Staging System. At diagnosis, 24.0% of the children were classified as underweight and 11.6% were overweight. Six months after diagnosis all children except those with stage 4s disease had a decrease in BMI z-score; difference in estimated marginal mean −0.73, P < .001. After 12 months an increase in BMI z-score was observed and by 2 years BMI z-score was significantly higher than BMI z-score at baseline; difference in estimated marginal mean 0.81, P = .007. At the last follow-up (median 5.6 years [range 3–7] after diagnosis) the proportion of children who were classified as underweight decreased to 8.7% and the proportion of children who were classified as overweight increased to 27.5%. The overall survival rate was 61.2%; however, BMI status did not predict survival. In multivariable Cox regression modeling, stage at diagnosis was the only predictor of survival; children diagnosed with stage 4 were less likely to survive (hazard ratio [HR] [95%CI]: 7.02 [1.7–29.0], P = .007). Almost a quarter of children with NB were underweight at diagnosis. However, we did not demonstrate a prognostic association between BMI status and survival. The high proportion of children who were classified as overweight at follow-up indicates a need for nutritional interventions to prevent potential late effects.